Potential effect of Commiphora myrrha resin on Eimeria labbeana-like-induced oxidative stress in Columba livia domestica - Abdel-Gaber, Rewaida; Albasyouni, Shurug; Santourlidis, Simeon; Al Quraishy, Saleh; Al-Shaebi, Esam (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEimeria infection in pigeons induces severe oxidative stress in intestinal tissues, disrupting the balance between oxidant and antioxidant systems and leading to cellular and physiological damage. The resin of Commiphora myrrha has long been recognized in traditional medicine for its therapeutic potential.PurposeThis study evaluated the protective effect of methanolic C. myrrha resin extract (MYE) against oxidative stress and cellular injury induced by Eimeria labbeana-like infection in pigeons.MethodsTwenty-five pigeons (300–380 g) were divided into five groups (G1–G5). Following infection, birds were treated daily with MYE. On day 8 post-infection, intestinal tissues were collected to assess oxidative stress markers, antioxidant enzyme activities, and inducible nitric oxide synthase (iNOS) expression via immunohistochemistry.ResultsInfection with E. labbeana-like markedly elevated intestinal levels of nitric oxide (NO), malondialdehyde (MDA), and hydrogen peroxide (H2O2), indicating enhanced oxidative stress. MYE administration significantly reduced these markers compared to infected controls. Concurrently, MYE enhanced antioxidant defense by increasing catalase (CAT), superoxide dismutase (SOD), and reduced glutathione (GSH) activities. Moreover, MYE modulated iNOS expression, suggesting regulation of inflammation-associated oxidative pathways.ConclusionMethanolic extract of C. myrrha resin effectively mitigated oxidative and related intestinal issues induced by E. labbeana-like infection in pigeon intestines. These findings highlight its potential as a natural source of antioxidant and anticoccidial agents for managing avian coccidiosis.